Comparative Mitogenome Analysis Reveals Mitochondrial Genome Differentiation in Ectomycorrhizal and Asymbiotic Amanita Species - Li, Qiang; He, Xiaohui; Ren, Yuanhang; Xiong, Chuan; Jin, Xin; Peng, Lianxin; Huang, Wenli (Frontiers in Microbiology, 2020)
In this present study, we assembled and analyzed the mitogenomes of two asymbiotic and six ectomycorrhizal Amanita species based on next-generation sequencing data. The size of the eight Amanita mitogenomes ranged from 37,341 bp to 137,428 bp, and we considered introns to be one of the main factors contributing to the size variation of Amanita. The introns of the cox1 gene experienced frequent gain/loss events in Amanita; and the intron position class cox1P386 was lost in the six ectomycorrhizal Amanita species. In addition, ectomycorrhizal Amanita species had more repetitive sequences and fewer intergenic sequences than asymbiotic Amanita species in their mitogenomes. Large-scale gene rearrangements were detected in the Amanita species we tested, including gene displacements and inversions. On the basis of the combined mitochondrial gene set, we reconstructed the phylogenetic relationships of 66 Basidiomycetes. The 6 ectomycorrhizal Amanita species were of single origin, and the 2 saprophytic Amanita species formed two distinct clades. This study is the first to elucidate the functions of the mitogenome in the evolution and ecological adaptation of Amanita species.